Displacement fields induced by penetrometer installation in an artificial soil. Issue 1 (March 2004) - Lehane, B. M.; Gill, D.R.
Abstract : This paper presents results from a laboratory experiment, which was devised to provide accurate measurements of the soil displacement paths followed during undrained installation of a penetrometer. The experiment combined the use of a precision video camera and a transparent soil with properties similar to those of a natural soft clay. The measured displacement paths are compared with an existing database of measurements and with predictions derived using the Shallow Strain Path Method. These comparisons reveal characteristics of penetrometer installation that will be of assistance to the advancement of currently developing numerical simulations of the installation process.